What is Metis? - Jay Timothy Dolmage (Disability Studies Quarterly, 2020)
Rhetoricians have come to understand that when we look through rhetorical history for what is most tense and polarizing, we most often come to stories about the body. Wherever we find the body rhetorically contested, and wherever we find rhetorical contestation about the body's role in meaning-making, we see intensely fraught negotiations. This should matter very much to those of us invested in disability studies work. In the last decade, some excellent rhetoricians have done this critical work. In this special issue, some excellent rhetoricians continue this critical work, bringing together rhetoric, writing studies, and disability studies – and the engine and the theme of this work is metis, cunning and adaptive intelligence. But what is metis, and why should it matter to disability studies?
Keywords: rhetoric; writing studies; metis; embodiment; teaching; pedagogy